2016
DOI: 10.1002/bmc.3751
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of paeoniflorin from total glucosides of paeony in Sprague–Dawley rats and spontaneously hypertensive rats by high‐performance liquid chromatography–tandem mass spectrometry: in vivo and in vitro studies

Abstract: Paeoniflorin is a well-known monoterpene glucoside in the herbal drug that exhibits a number of biological activities. The pharmacokinetic characteristics of paeoniflorin from total glucosides of paeony in spontaneously hypertensive rats (SHR) are still unclear. It is essential to investigate the in vivo and in vitro pharmacokinetic differences of paeoniflorin from total glucosides of paeony in Sprague-Dawley (SD) and SHR. The in vivo pharmacokinetic data were analyzed using DAS 2.0 software and the in vitro m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 21 publications
2
8
0
Order By: Relevance
“…Blood samples (~0.1 ml) were collected from jugular vein of rats at pre‐dose (0), 5, 15, 30, 60, 120, 240, 360, 480, 720 and 1440 min. The blood samples were immediately centrifuged at 4500 rpm for 10 min at 4°C and the plasma samples were transferred carefully from each collection and stored at −20°C until analysis (Li et al, ; Xiong & Wang, ).…”
Section: Methodsmentioning
confidence: 99%
“…Blood samples (~0.1 ml) were collected from jugular vein of rats at pre‐dose (0), 5, 15, 30, 60, 120, 240, 360, 480, 720 and 1440 min. The blood samples were immediately centrifuged at 4500 rpm for 10 min at 4°C and the plasma samples were transferred carefully from each collection and stored at −20°C until analysis (Li et al, ; Xiong & Wang, ).…”
Section: Methodsmentioning
confidence: 99%
“…Blood samples (approximately 0.1 ml) were collected from jugular vein of rats in heparinized tubes at 5, 15, 30, 60, 90, 120, 240, 360, 480, 720 and 1,440 min after dosing. The blood samples were immediately centrifuged at 1,280 g for 15 min at 4°C to obtain the plasma, which was then stored at −20°C until analysis (Li et al, 2019; Xiong & Wang, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Radix Paeoniae Alba (RPA), with paeoniflorin as principal bioactive component, is a traditional Chinese medicine that lowers blood pressure and exhibits anti-inflammatory and antioxidative properties, among others [ 8 ]. An increasing number of studies found that paeoniflorin or extract of RPA exerts a positive effect on cardiovascular function [ 9 11 ].…”
Section: Introductionmentioning
confidence: 99%